The role of corporate citizens in fighting poverty: An ordonomic approach to global justice - Ingo Pies; Stefan Hielscher (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2008)
Drawing on an ordonomic approach, this paper argues that a theory of global justice should incorporate as a pivotal cornerstone a theory of corporate citizenship which constructively addresses business firms as agents of social value creation. We argue that, instead of relying exclusively on arguments of obligation, a theory of global justice should primarily formulate arguments of prudence in order to live up to the fundamental incentive structures that govern modern competitive markets to which we owe much of our last two centuries' moral and material progress. We develop our argument with critical reference to Thomas Pogge's seminal work on global justice.
Keywords: A12; A13; D02; D63; F02; F35; O40; 330; Global justice; development cooperation; development ethics; foreign aid; poverty reduction; ordonomics; social dilemma